Predicting Gentrification in the Historic Center of a Heritage City: Case study Cuenca – Ecuador - Orellana-Alvear, Boris (2024)
Gentrification is an urban phenomenon that displaces the original inhabitants of a neighborhood due to regeneration processes. In this analysis carried out in the historic center of the heritage city of Cuenca, the beginning of the process does not necessarily respond to a significant transformation of the architecture. It has been proven that the phenomenon arises invisibly due to changes in the demographic composition of the neighborhood. The methodology of this research requires the correlation of census data for each minimum applicable unit known as a block. This information is contrasted with historical photographs available on the Google platform. The significant contribution to the concept of gentrification results in a method that allows identifying and predicting the phenomenon, more important than its visual-late diagnosis.